Fislake, Martin - (:unkn) unknown (My University, 2026)
Martin Fislake was trained as a mechanic during an apprenticeship in Germany before he got his first and second teacher exam as a vocational teacher for mechanical engineering in 1993. Following that he was hired in 1993 at the University of Koblenz and is since then continuously working as a full-time lecturer and head of the technology education department where he teaches primary and lower secondary student teachers. In 2001 he received his doctoral in engineering education, higher education didactics and educational economics from the University of Koblenz. In addition, he operates a technology-oriented summer school comprising about one hundred courses a year for children and youth as an education and research project. Currently he writes and presents widely on issues of technology education with a focus on educational robotics and his out of school project technikcamps.